Prediction of Performance and Emission of Gasoline Engine Fueled with a Gasoline-Ethanol-Methanol Mixture Using One Dimensional Engine Modelling Based on Engine Test Results - Rudi Cahyo Nugroho; Respatya Teguh Soewono; Ade Kurniawan; Muhammad Ma'ruf; Mohammad Amanta Kumala Sakti; Suherman Mukti; Abid Paripurna Fuadi; Bagus Anang Nugroho (Universitas Muhammadiyah Magelang, 2024)
The depletion of petroleum reserves as the basic raw material for gasoline production has driven studies into alternative fuels. One of the alternative fuels is alcohol, both ethanol and methanol. Due to their liquid form and physical-chemical properties similar to gasoline, small modifications to the engine are required. This paper will explain the effect of using a mixture of gasoline (in this case, RON 98 gasoline with methanol or methanol on engine performance and emissions. The fuel mixtures are as follows: G100, E10, E20, E30, M10, M20, M30. AVL Boost simulation software was used as a tool for 1-dimensional engine modelling, where the modeling is based on engine testing with G100 fuel. The results show that with increasing ethanol-methanol composition, torque and power decrease, and SFC increases. On the emission side, CO, CO2, and HC were decreased and NOx increased.